Assessment of Integrated Agriculture–Aquaculture Scenarios for Aquatic Animal Cultivation and Floating Rice in Coastal Zones - Heriansah Heriansah; Indra Cahyono; Nursidi Nursidi; Awaluddin Awaluddin; Fathuddin Fathuddin (Journal Omni-Akuatika, 2026)
This study represents a potentially groundbreaking exploration into the dual integration of agriculture and aquaculture (IAA) systems in brackish water. The objective of this work was to assess the production performance of the IAA system under various species combination scenarios, which are pivotal in multi-species cultivation. Conducted over an 80-day period, this study employed three species combination scenarios: milkfish and rice (Scenario 1), milkfish, tiger shrimp, and rice (Scenario 2), and milkfish, tiger shrimp, mussel, and rice (Scenario 3). A floating-bed system was utilized for rice cultivation in all scenarios. The pilot scale experiment was meticulously designed, including tarpaulin ponds, acclimatization, feed, and aeration to establish a conducive environment within the system. Results revealed proportional species growth, with the mortality rate (MR) of milkfish, tiger shrimp, and rice showing no significant impact (P > 0.05) from species combinations. However, significant differences (P < 0.05) were observed in the weight gain (WG) and specific growth rate (SGR) of milkfish, as well as the height gain (HG) of rice among species combinations. Nutrient removal efficiency (NRE) for nitrogen and phosphorus increased significantly with the combined number of species. Species combinations also had a significant effect on feed efficiency ratio (FER). All observed parameters in scenario 3 (IAA) demonstrated superiority, making it a more practical approach for the IAA model in coastal zones. This study validates an optimal species combination model, providing a scalable framework to advance productivity and nutrient efficiency in future integrated coastal aquaculture systems.